Sensitivity of the autobiographical work "The History of the Past" by M. Staryskyi (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article, in terms of the features of psychopoetics, examines the worldly view of a young Starytsky presented in his autobiographical book «Out of mist of past». The author of the article highlights that the childhood memory of Starytsky, was recanting mainly the best moments from his childhood; namely his caring grandmother, the adult conversations with his grandfather, and gentle care of the nurses. In the article the author analyzed the phenomenon of sensibility of creative personalities as the sensual level of an individual’s perceived understanding of the world. From this perspective, Starytsky had a heightened sensibility and awareness.
Keywords: psychopoetics; sensibility; autobiographical work